2020
DOI: 10.17509/mimbar-sd.v7i3.29100
|View full text |Cite
|
Sign up to set email alerts
|

Developing Elementary School Teacher Competence in Making Music Learning Media Using Scratch Application: An Action Research

Abstract: The development of technology and information demands elementary school teachers to be able to make and teach technology-based musical instruments so that the development of technology and information can be used in the learning process. Elementary school teachers also have problems teaching musical composition using ensemble musical instruments. Teachers also lack strategies and media to teach musical instruments, so they need to have ideas for developing technology-based musical instruments. This study aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
5
0
3
Order By: Relevance
“…With 38 primary school teachers working in Indonesia, Julia et al (2020) carried out music design applications with the Scratch program in order to improve the technology-based music education skills of the teachers. At the end of the research, it was concluded that the teachers could easily implement the relevant program and thus enrich their music teaching environment by improving their technological skills.…”
Section: Discussionmentioning
confidence: 99%
“…With 38 primary school teachers working in Indonesia, Julia et al (2020) carried out music design applications with the Scratch program in order to improve the technology-based music education skills of the teachers. At the end of the research, it was concluded that the teachers could easily implement the relevant program and thus enrich their music teaching environment by improving their technological skills.…”
Section: Discussionmentioning
confidence: 99%
“…Pembelajaran berbasis digital yang memadukan teknologi ke dalam proses pembelajaran bertujuan untuk mengimbangi tren perubahan teknologi di era digital yang diharapkan dapat mendorong pengetahuan dan keterampilan siswa melalui peningkatan efektivitas dan efisiensi (Ghory & Ghafory, 2021;Gusrayani et al, 2019). Adanya teknologi dapat memikat siswa menjadi lebih terlibat dalam partisipasi yang lebih aktif di kelas, namun pendidik juga harus memastikan bahwa teknologi membuat siswa lebih mudah untuk menerapkan pengetahuannya di lingkungan mereka (Julia et al, 2020;Montrieux et al, 2015;Roy, 2019;Uluyol & Şahin, 2016;Vanderlinde & van Braak, 2010). Salah satu cara untuk memicu minat belajar siswa dengan menggunakan teknologi adalah melalui penggunaan media audio visual.…”
Section: Pendahuluanunclassified
“…In this sense, innovative/disruptive pedagogical trends in music education follow the same dynamics as those in other areas, with Information and Communication Technology (ICT) related initiatives monopolizing the discourse when talking about disruption (Ocaña-Fernández et al, 2020). Nonetheless, due to the specificity of music, the interest in technological integration is more focused on the creation of artistic products (Julia et al, 2020). However, we can also find academic texts discussing innovation and disruptive proposals in music education from positions (e.g.…”
Section: Theoretical Framework/backgroundmentioning
confidence: 99%